Haemophilic Arthropathy In Comparison To Vata Rakta: A Comprehensive Exploration - Kumar, Arun; Rani, Sonia; Jain, Seema; Varsha, Varsha (Journal of Neonatal Surgery, 2025)
Haemophilic arthropathy is a chronic joint condition resulting from recurrent bleeding into joint spaces, predominantly affecting individuals with haemophilia. This condition leads to progressive joint damage, pain, and reduced mobility. This condition, deeply researched in modern medicine, contrasts with the Ayurvedic concept of Vata Rakta, which manifests as a painful condition involving blood (Rakta) and the Vata Dosha. While the two conditions are distinct in their etiology and pathophysiology, they share certain clinical features, such as bleeding and joint involvement. This article provides an in-depth review of haemophilic arthropathy and Vata Rakta, exploring their pathophysiology, clinical manifestations, diagnostic approaches, and treatment protocols from both modern and Ayurvedic perspectives. The review aims to bridge traditional and contemporary knowledge systems for a better understanding of these conditions